Gaming the SySTEM: The Relationship Between Video Games and the Digital and STEM Divides. Issue 5 (July 2020) - Ball, Christopher; Huang, Kuo-Ting; Cotten, Shelia R.; Rikard, R. V.
Science, technology, engineering, and mathematics (STEM) careers are increasingly vital for countries, such as the United States and United Kingdom, to remain innovative and productive in the 21st century. Despite the growing demand and lucrative nature of STEM fields, minorities have remained traditionally underrepresented in STEM careers, possibly due to digital divide factors. In this study, we use social cognitive theory to explore the potential of video gameplay to provide a means of increasing minority students' comfort with information and communication technologies, thereby increasing their positive STEM attitudes. Data were gathered during a large-scale computing intervention in an elementary school district in the southeastern United States. The results indicate that video game experiences may influence STEM attitudes via the mediating role of computer self-efficacy and emotional costs. Video gameplay, including games for entertainment, may be beneficial for young digitally divided populations as it may provide them with positive enactive experiences with technology.